beta-Lipotropin as a prohormone for the morphinomimetic peptides endorphins and enkephalins. - Lazarus, L H (1976)
The hypophysial homomeric peptide beta-lipotropin (beta-LPH-[1-91]) has no morphinomomimetic activity in a bioassay (myenteric plexus-longitudinal muscle of the guinea pig's ileum) or binding assays with stereospecific opiate-receptors of rat brain synaptosome preparations. Incubating beta-LPH-[1-91] at neutral pH with the supernatant aqueous extracts of rat brain generates (fragments of beta-LPH with) morphinomimetic activity in the same assay systems. These results are related to the recently recognized structural relationships between beta-LPH, the newly isolated peptides met-enkephalin (beta-LPH-[61-65]) and alpha-endorphin (beta-LPH-[61-76]) and also to the biologically active fragments of analogs: beta-LPH-[61-64], beta-LPH-[61-65[-NH2, (Met(O)65)-BETA-LPH-[61-65], beta-LPH-[61-69], and beta-LPH-[61-69]. Enzymatic biogenesis of these morphinomimetic peptides would preclude localizing them as such in cellular or subcellular elements with currently available methodology.